A searching and automatic video tagging tool for events of interest during volleyball training sessions - Salim, F.; Haider, F.; Tasdemir, S. B. Y.; Naghashi, V.; Tengiz, I.; Cengiz, K.; Postma, D.; van Delden, R.; Reidsma, D.; Luz, S.; van Beijnum, B.-J. (ICMI '19: 2019 International Conference on Multimodal Interaction, 2019)
Quick and easy access to performance data during matches and training sessions is important for both players and coaches. While there are many video tagging systems available, these systems require manual effort. This paper proposes a system architecture that automatically supplements video recording by detecting events of interests in volleyball matches and training sessions to provide tailored and interactive multi-modal feedback.